Group Conflict Theory in a Longitudinal Perspective: Analyzing the Dynamic Side of Ethnic Competition. Issue 1 (March 2013) - Lancee, Bram; Pardos-Prado, Sergi
One of the most established approaches to explain attitudes toward immigration is group conflict theory. However, even though the theory was articulated in dynamic terms, previous research has almost exclusively tested it through cross-sectional analyses. The aim of this study is to disentangle the dynamic character of ethnic competition from more permanent determinants of ethnic threat. The findings show that a remarkable variation of concern over immigration, usually attributed to permanent positions of economic vulnerability, disappears when within-person variation is modeled. In line with a dynamic approach of ethnic competition, becoming unemployed or being laid off increases concern over immigration. This effect is independent of social class.